The social and economic cost of divorce from the perspectives of the employees at social development committees in Riyadh City - Elheky, Mamdouh Abdalla (Journal of Humanities & Social Sciences, 2023)
This study attempted to examine the social and economic cost of divorce and to identify the factors that contributed to the spread of divorce in recent years and the ways to reduce this phenomenon. To achieve the objectives of the study, the researcher used the descriptive analytical approach. The questionnaire was used as the data collection tool from the research sample that consisted of the employees of (16) Social Development Committees (SDCs), randomly selected out of (55) SDCs in Riyadh city. The questionnaire was distributed on (104) employees who served as the research sample. The answered questionnaires were then collected and statistically analyzed via SPSS software. The results showed that the most common factors that contributed to the spread of divorce from the respondents’ perspective, respectively, are the failure to choose the appropriate partner, marital infidelity, modern social media, financial and economic burdens of the life and the cultural openness of women as a result of their exit to work. The results also showed that divorce has very important social and economic consequences, most notably; the disintegration of the family and the homelessness of children, the spread of crime and vice in the society, the poor social relations with those around as well as the loss of the financial source for the family, the increased financial burdens on the divorced woman, the increased financial burdens of the country and the increased expenditure on the man. Furthermore, the results showed that the most effective ways to reduce the phenomenon of divorce include increasing qualification programs for those who are about to marry, the choice of the culturally-fit, financially-fit and socially-fit partner, disseminating the Islam-based sexual culture and raising the awareness of its importance and cultivating the family culture from a young age. The study recommended the necessity of disseminating awareness, counseling, rehabilitation and educational programs that highlight the negative effects of divorce and contribute to reducing it.
Keywords: Divorce; Economic Cost of Divorce; Social Cost of Divorce; Social Development Committees